Restoration as the spirit of Islamic justice - Fallon, Andrew (Contemporary justice review, 2020)
Over the last few decades, scholars in the conflict resolution field have begun to appreciate religion’s role in promoting the values, beliefs and practices of peace and nonviolence. Though scholars have identified myriad Islamic sources of conflict resolution, few have engaged with the restorative justice tradition directly. In the following paper, I identify the Islamic foundations of restorative justice through an examination of the restorative themes in the Qur’an and an analysis of Islamic crime and punishment. Any discrepancies between the restorative framework and the Islamic framework are discussed. I then identify and illustrate Islamic restorative practice in the Palestinian indigenous tradition of sulha. This paper demonstrates that in both theory and practice, what is understood as Islamic justice can also be conceptualised as an interpersonal, restorative justice.